Brain Microvascular Endothelial Cell-Derived HMGB1 Facilitates Monocyte Adhesion and Transmigration to Promote JEV Neuroinvasion - Zou, Song-Song; Zou, Qing-Cui; Xiong, Wen-Jing; Cui, Ning-Yi; Wang, Ke; Liu, Hao-Xuan; Lou, Wen-Juan; Higazy, Doaa; Zhang, Ya-Ge; Cui, Min (Frontiers in Cellular and Infection Microbiology, 2021)
Infection with Japanese encephalitis virus (JEV) induces high morbidity and mortality, including potentially permanent neurological sequelae. However, the mechanisms by which viruses cross the blood-brain barrier (BBB) and invade into the central nervous system (CNS) remain unclear. Here, we show that extracellular HMGB1 facilitates immune cell transmigration. Furthermore, the migration of immune cells into the CNS dramatically increases during JEV infection which may enhance viral clearance, but paradoxically expedite the onset of Japanese encephalitis (JE). In this study, brain microvascular endothelial cells (BMECs) were utilized for the detection of HMGB1 release, and leucocyte, adhesion, and the integrity of the BBB in vitro. Genetically modified JEV-expressing EGFP (EGFP-JEV) and the BBB model were established to trace JEV-infected immune cell transmigration, which mimics the process of viral neuroinfection. We find that JEV causes HMGB1 release from BMECs while increasing adhesion molecules. Recombinant HMGB1 enhances leukocyte-endothelium adhesion, facilitating JEV-infected monocyte transmigration across endothelia. Thus, JEV successfully utilizes infected monocytes to spread into the brain, expanding inside of the brain, and leading to the acceleration of JE onset, which was facilitated by HMGB1. HMGB1-promoted monocyte transmigration may represent the mechanism of JEV neuroinvasion, revealing potential therapeutic targets.